Isothermal omega kinetics in beta-titanium alloys. (4th March 2017) - Coakley, James; Seong, Baek-Seok; Dye, David; Ohnuma, Masato
Abstract: Small angle X-ray and neutron scattering provide a non-localised quantitative analysis of nanoscale precipitates in Ti-7Mo at.% and Gum metal, a Ti-Nb based alloy. The nucleation and coarsening kinetics are more rapid in the Ti-Nb alloy than the Ti-Mo alloy, presumably as Nb diffuses more rapidly than Mo in Ti. Therefore Mo-based -Ti alloys are more stable during ageing than Nb-based -Ti alloys. To the authors' knowledge, this represents the first publication quantifying size, volume fraction and element partitioning in Gum metal.